Contextually responsive and knowledge-focused teaching: disrupting the notion of ‘best practices’ - Jacobs, Cecilia (Critical Studies in Teaching and Learning, 2023)
The notion that universal ‘best practices’ underpin higher education teaching is problematic. Although there is general agreement in the literature that good teaching is not decontextualised but rather that it is responsive to the context in which it occurs, generic views of teaching and learning continue to inform practices at universities in South Africa. This conceptual paper considers why a decontextualised approach to higher education teaching prevails and interrogates factors influencing this view, such as: the knowledge bases informing this approach to teaching, the factors from within the higher education sector that shape this approach to teaching, as well as the practices and Discourses prevalent in the field of academic development. The paper argues that teaching needs to be both contextually responsive and knowledge- focused. Disrupting ‘best practices’ approaches require new ways of undertaking academic staff development, which are incumbent on the understandings that academic developers bring to the enterprise.